Tolerância de cultivares de cana-de-açúcar à erradicação química - Adriano, R. C.; Azania, C. A.M.; Pinto, L. R.; Perecin, D.; Azania, A. A.P.M. (FapUNIFESP (SciELO), 2013)
Knowledge of the minimum rate of glyphosate required to eradicate sugarcane ratoons can reduce the amount of herbicide used. To confirm this hypothesis, this study aimed to investigate the tolerance of different sugarcane cultivars to chemical eradication, at different glyphosate rates. The experiment was conducted in a randomized block design in a split-plot scheme, with four replications. The sugarcane cultivars (IACSP94-2094, IACSP94-2101, IACSP93-3046, IACSP94-4004, IAC86-2480, and RB72454) were allocated in plots and the glyphosate rates (0, 1,440, 2,160, 2,880, 3,600, and 4,320 g ha-1), in the sub plots. The traits evaluated were signs of poisoning symptoms; total chlorophyll content, plant height, percentage of dead tillers, and dry weight of the plants. At 45 days after application (DAA), the glyphosate rate of 1,440 g a.e. ha-1 eradicated the cultivars IACSP94-2094 and IACSP94-2101, as well as RB72454 with application of 2,160 g a.e. ha-1. Application of glyphosate 2,880 g a.e. ha-1 eradicated both IACSP93-3046 and IAC86-2480 and glyphosate 3,600 g a.e. ha-1 eradicated IACSP94-4004. The most tolerant cultivar was IACSP94-4004, eradicated at the rate of 3,600 g. a.e. ha-1. This confirms the hypothesis that knowing the cultivar's tolerance leads, in practice, to a smaller amount of herbicide applied to the environment, which also reduces production costs.
Tolerance of sugarcane cultivars to chemical eradication
Keywords: Glyphosate; Ratoons; Saccharum spp; Sugarcane renovation